(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This study investigates the influence of mass media consumption on mental health indicators - anxiety, stress, depression, and aggression - among secondary school students (grades 10–11) and university students in Uzbekistan. A cross-sectional comparative design was employed with 70 participants (n = 35 per group). Three validated instruments were administered: the Spielberger - Khanin Anxiety Inventory (STAI), the Depression Anxiety Stress Scales-21 (DASS-21), and the Buss–Durkee Aggression Inventory. University students demonstrated significantly higher reactive anxiety. Regarding aggression, indirect aggression and resentment were significantly higher in schoolchildren. Strong positive correlations were identified between anxiety types and DASS-21 subscales. These findings highlight differential media-related psychological burden across educational groups and underscore the need for targeted mental health interventions.